PENGARUH MEKANISME KONTROL INTERNAL TERHADAP EARNINGS MANAGEMENT - Agustin, Meritha Yuli (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research is meant to test the influence of internal control mechanisms i.e.: ownership structure, capital structure, and growth opportunity in go public food and beverages companies. The result of this research is expected to be useful for the development of science as well as the management of the company. The samples in this research are the food and beverages companies which go public in 2007 up to 2011with criteria negative net income and positive net income during 2007 â 2011 periods, the companies which issue financial report consecutively and do not issue financial report consecutively during 2007 â 2011 periods. There are 8 food and beverages companies which are used as sample in this research from these criteria. Based on the result of t test, it indicates that only ownership structure variable which has no influence to the Earnings Management and capital structure and growth opportunity variables which have influence to the Earnings Management on food and beverages companies which go public in the Indonesia Stock Exchange. Keywords: Earnings Management, Ownership Structure, Capital Structure, Growth Opportunity